Latex allergy in health care workers: prevalence and knowledge at a tertiary teaching hospital in a developing country - Ismail, Nazir Ahmed; Hoosen, Anwar Ahmed; Mehtar, Shaheen (International Journal of Infection Control, 2009)
Latex allergy is a concern from an occupational safety aspect because it affects compliance of glove usage, which directly influences infection control practices aimed at providing safe medical care for both the health care worker (HCW) and patient. The Dr George Mukhari Hospital (DGM) in Pretoria has a staff complement of 1500 doctors and nurses who use latex gloves occasionally or regularly. The objective for this study was to evaluate the current prevalence of latex allergies and staff awareness of latex glove allergies as well as the availability of alternatives.Laboratory records were reviewed and a crude prevalence was calculated at <1% over the study period. Interviews assessing HCW knowledge and practices regarding latex glove allergy and alternatives were performed using a questionnaire. Results from the interviews identified numerous gaps in knowledge regarding latex allergies and alternatives even amongst those who had latex allergies. However, those who were aware of their latex allergy had a lower risk of non-compliance with use of gloves in the prevention of infection. Thus greater efforts are required to educate HCWs regarding latex allergies and consideration should be given to the use of non-latex gloves in high use areas to reduce future latex allergy development which can affect the HCW’s occupational and social functioning.